Solanum lycopersicum CLASS-II KNOX genes regulate fruit anatomy via gibberellin-dependent and independent pathways. (16th November 2022) - Shtern, Amit; Keren-Keiserman, Alexandra; Mauxion, Jean-Philippe; Furumizu, Chihiro; Alvarez, John Paul; Amsellem, Ziva; Gil, Naama; Motenko, Etel; Alkalai-Tuvia, Sharon; Fallik, Elazar; Gonzalez, Nathalie; Goldshmidt, Alexander
Abstract: The pericarp is the predominant tissue determining the structural characteristics of most fruits. However, the molecular and genetic mechanisms controlling pericarp development remain only partially understood. Previous studies have identified that CLASS-II KNOX genes regulate fruit size, shape, and maturation in Arabidopsis thaliana and Solanum lycopersicum . Here we characterized the roles of the S. lycopersicum CLASS-II KNOX ( TKN-II ) genes in pericarp development via a detailed histological, anatomical, and karyotypical analysis of TKN-II gene clade mRNA-knockdown ( 35S:amiR-TKN-II ) fruits. We identify that 35S:amiR-TKN-II pericarps contain more cells around their equatorial perimeter and fewer cell layers than the control. In addition, the cell sizes but not the ploidy levels of these pericarps were dramatically reduced. Further, we demonstrate that fruit shape and pericarp layer number phenotypes of the 35S:amiR-TKN-II fruits can be overridden by the procera mutant, known to induce a constitutive response to the plant hormone gibberellin. However, neither the procera mutation nor exogenous gibberellin application can fully rescue the reduced pericarp width and cell size phenotype of 35S:amiR-TKN-II pericarps. Our findings establish that TKN-II genes regulate tomato fruit anatomy, acting via gibberellin to control fruit shape but utilizing a gibberellin-independent pathway to control the size of pericarp cells. Abstract : Tomato CLASS-II KNOX genes regulate fruit and pericarp anatomy via both gibberellin-dependent and independent pathways.